Measurement of contrast sensitivity using the M&S smart system II compared with the standard Pelli–Robson chart in patients with primary pterygium - Hilmi, Mohd Radzi; Khairidzan, Mohd Kamal; Che Azemin, Mohd Zulfaezal; Azami, Muhammad Hanafi; Ariffin, Azrin Esmady; , (Universitas Indonesia, 2018)
Background: Contrast sensitivity (CS) is widely used as a measure of visual function in research and clinical settings. CS is regarded as an important visual parameter, detecting subtle reductions in vision prior to significant reduction in visual acuity. Methods: We examined the agreement between the gold-standard Pelli–Robson chart and a computerized test termed the M&S Smart System II (MSSS-II) in patients with primary pterygium. Ninety-three patients (93 primary pterygium eyes) who visited an ophthalmology clinic were selected. The patients were randomly assessed for CS using the MSSS-II or Pelli–Robson chart. The primary outcome was agreement in log units between these two tests in the assessment of CS in patients with primary pterygium. Results: The mean and standard deviation of CS measurement in the two tests were comparable (1.22 ± 0.56 vs. 1.21 ± 0.57 log units, respectively, p = 0.083). The Bland–Altman plot revealed that the mean difference between the two charts was 0.0016 log units (standard deviation: 0.009 log units) with narrow limits of agreement of −0.0186 to 0.0186. Conclusions: MSSS-II provides an alternative for the clinical assessment of CS using a computerized method that describes the status of visual function in patients with primary pterygium.